Preparation for return to normal operations: mitigating the impacts of COVID-19 to aviation safety - Li, Wen-Chin; Braithwaite, Graham (Cranfield University, 2022)
The objective of implementing an airline FDM programme is to shift from a purely reactive approach to safety based on crew€™s reporting incidents to a proactive approach of identifying potential risks and implementing mitigation measures. A FDM programme enables to predict the probability and severity of occurrences for developing an effective SMS within an airline. To mitigate the impacts of the pandemic, tailored training sessions must be implemented, and airlines should strive to avoid complex flight deck and operational environments, where practicable.
Keywords: Aviation Safety'; 'Flight Data Monitoring'; 'Operational Proficiency'; 'Safety Resilience'